The role of immersive technologies in increasing labour productivity on the example of augmented and virtual reality - N. G. Merzlikin (Вестник университета)
The article analyses the role of immersive technologies in increasing productivity in enterprises. Economic growth is determined not only by productive forces, but also by the rational use of human labour and achievements of scientific and technological progress. The author has examined the experience of using digital tools relevant to the market that improve productivity – virtual and augmented reality. These technologies have a significant impact on labour productivity and contribute to enhancing performance indicators of production operations. The global practice of applying immersive technologies in enterprises demonstrates a wide range of areas of their use. Thus, augmented and virtual reality are in demand in mechanical engineering, energy extraction, logistics, design of facilities and production lines. In essence, these technologies expand the boundaries of human capabilities in interaction with virtual and augmented spaces, providing unique management tools for solving tasks of varying complexity, and have significant potential in the context of better productivity. Based on the results of the analysis, the key functions of augmented and virtual reality in industry have been identified, and the structure of the functional usage of immersive technologies to increase productivity has been developed.